Consumer’s perception towards corporate social responsibility and its impact on buying behaviour: a study of Sarawak Energy Berhad/ Mohd Amirul Adenan - Adenan, Mohd Amirul (2015)
Corporate social responsibility is defined as the firm’s responsibility to maximize their positive impact and to minimize negative effects by contributing to society along with the concern for the society’s needs and wants in the long-term perspective. In this study the perception of CSR based on the dimensions of the CSR itself will be investigated. The impact of these dimensions will also be analysed. The location of this study will be on the headquarters of Sarawak Energy Berhad so the result will not be generalized. This research will be using frequency statistics, descriptive analysis, reliability analysis, multiple regression analysis and Pearson’s correlation analysis in answering the objective of the research. Recommendations will be made based on the findings.